2017
DOI: 10.1002/asi.23938
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthiness attribution: Inquiry into insider threat detection

Abstract: Insider threat is a “wicked” contemporary organizational problem. It poses significant threats to organizational operations and information security. This article reviews insider threat research and outlines key propositions to conceptualize the interpretation of dynamic human information behavior in an organizational setting, which represent an integration of trustworthiness and human sensors’ attribution in close relationships. These propositions posit that when a focal individual violates integrity‐based tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Wheelan [77] also confirmed that groups containing 3 to 6 members were significantly more productive and developmental than larger groups. The present study thus suggests designing experiments to facilitate small group situations where members are given opportunities to interact closely [41], which also follows the proposition postulated by Ho, Kaarst-Brown et al [42] that "close relationships" are required to afford groups the opportunities to unknowingly observe subtle language-action cues that may indicate a lowering of trustworthiness (p. 276).…”
Section: Close Relationshipssupporting
confidence: 74%
See 4 more Smart Citations
“…Wheelan [77] also confirmed that groups containing 3 to 6 members were significantly more productive and developmental than larger groups. The present study thus suggests designing experiments to facilitate small group situations where members are given opportunities to interact closely [41], which also follows the proposition postulated by Ho, Kaarst-Brown et al [42] that "close relationships" are required to afford groups the opportunities to unknowingly observe subtle language-action cues that may indicate a lowering of trustworthiness (p. 276).…”
Section: Close Relationshipssupporting
confidence: 74%
“…One's trust towards an individual can be impacted (i.e., reduced or lost) as a result of the violation of competence in the performance of obligations, or the violation of integrity [42]. Competence-based trust violations occur when group members feel betrayed because a member does not fulfill obligations or expectations.…”
Section: Group Trust In Leader Member Exchangementioning
confidence: 99%
See 3 more Smart Citations